Surgical management of extramural ectopic ureter by modified colposuspension following ureteroneocystostomy in a young female Siberian Husky dog - Jeong, In Seong; Rahman, Md. Mahbubur; Kim, Hwangmin; Kim, Sehoon (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Postoperative complication of extramural ectopic ureters (EEUs) with persistent urinary incontinence (UI) is common in Siberian Huskies. This case report was aimed at reporting the successful correction procedure of EEU in Siberian Huskies by surgical procedure. Materials and methods: A three-month-old and weighing 7.9 kg Siberian Husky dog was presented with history of an acute dermatitis around the genitals, swelling of the genitals and dribbling urination. Abdominal radiographs, ultrasonography, and 3D computed tomography scanning revealed presence of the ectopic ureter with urinary incontinence. Ureteroneocystostomy was applied as the first choice of corrective procedure in this case, and clinical sings were corrected apparently after surgery. Unfortunately, UI with cystitis was developed two months postoperatively. To correct the condition, surgical procedure of colposuspension with ovarianhystectomy and cystopexy was opted. Results: Post-operative progression showed good prognosis and the dog recovered fully. Follow up checkup of the patient after 4 months postoperative and follow up phone call 27 months later did not reveal any abnormalities. Conclusion: This case report recommends surgical procedure of modified colposuspension following ureteroneocystostomy to correct EEUs and its postoperative complication. http://doi.org/10.5455/javar.2017.d214